Pengaruh Kompetensi Guru terhadap Pendidikan Karakter Di TPQ - Mahrus Hadi (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2022)
The teacher is one of the important factors in the implementation of classroom learning, without a teacher the learning process cannot be carried out. The teacher has an important role in the learning process because the teacher not only delivers the subject matter, but the teacher also provides character education to students, namely educating students to become smart citizens and have a good personality. Teachers must know and be able to apply innovative and fun learning models and methods. This study aims to determine: 1) To determine the competence of TPQ teachers 2) to determine the character education of TPQ students 3) The effect of teacher competence on character education of students in TPQ.The most relevant approach to this research is the socio-cultural approach. The material taught may be a package from an institution that holds policy authority, but the way of delivering the material is the responsibility of the educator. The success of the packaged material is about how the methods of educators are to spread, transfer knowledge so that it can be fully accepted by students according to the level of education